THE INFLUENCE OF PASANG RI KAJANG IN THE ANDINGINGI RITUAL ON THE RELIGIOSITY OF THE KAJANG AMMATOA TRIBE COMMUNITY - Riswandi, Riswandi; Abidin, Aslan; Saguni, Suarni Syam (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
This research aims to describe the influence of Pasang ri Kajang in the Andingingi ritual on the Kajang community using Cliffort Greetz's theory of religion and culture using descriptive qualitative research methods by describing the data obtained based on the theory used. The data source in this research is Pasang ri Kajang in Andingingi ritual. Data collection by means of observation, interview techniques, and documentation techniques. This study found that the influence of Pasang ri Kajang in the Andingingi ritual found such as (1) quality of life, (2) style and moral sense, and (3) character and outlook on life.